The practice of real estate agency / Haslinah Yacob - Haslinah, Yacob (1984)
In recent years, real estate transactions have been increasing substantially in Malaysia, whereby in Kuala Lumpur it is more prominent. As the volume of sales have increased, the investor's choice as to the use of professional assistance has varried .Investors are getting more particular in choosing the right person to advice him on the investment potentiality of a property. The vendor would want his particular real estate to be sold at the shortest time possible and of course at the highest price he can get. The same applies to the purchasers as they would demand the best from their money's worth. The potential purchaser would then need a wide knowledge in the real estate market in order to get the best buy. Therefore the estate agent is both a credit to both th vendors and the purchasers as they have foresight, originality, keeness of perception and dogged persistence to bring deals into being. The objective in preparing this dissertation is to give a brief guideline to anybody who might be interested in operating a real estate agency firm. I believe being a real estate agent is interesting and challenging.